Features of the Relationship Between Metacognitive Monitoring and Metacognitive Control - Avhustiuk, Mariia (Visnyk of V.N. Karazin Kharkiv National University. Series Psychology, 2021)
The research studies the peculiarities of the relation between metacognitive monitoring and metacognitive control. The study focuses on some theoretical and methodological aspects of the relationship between metacognitive monitoring and control. The article presents an analysis of metacognitive monitoring and control concepts, their distinct functional features, the processes of their functioning, and the peculiarities of the interaction between these components of metacognition. Metacognitive monitoring as a subjective assessment of one's own cognitive processes and knowledge cannot be considered separately from metacognitive control over the strategic regulation of cognitive operations and resources. As a result, metacognitive monitoring processes are an important condition for updating metacognitive control. Thanks to properly organized highly effective metacognitive monitoring, students can at the metacognitive level study cognitive features of knowledge acquisition and use appropriate learning strategies. With the help of metacognitive control, students can use metacognition to regulate their own activities at the cognitive level. The need to study the features of this interaction was due to the importance of continuing the theoretical analysis of the basics of metacognitive monitoring, substantiation of its components, clarifying of the relationship with the effectiveness of educational activities and etc. The results of the theoretical analysis found in the study play a significant role in this relationship understanding. We can assume that the results of the theoretical analysis found in the study play a significant role in the process of understanding such issues.